1991
DOI: 10.1017/s0031182000060431
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of murineMesocestoides cortiinfection by bacterial lipopolysaccharide and interferon-γ

Abstract: Many liver-invasive parasites cause extensive liver damage which may result in an impaired ability to catabolize endotoxin. The influence of endogenous endotoxin on the progress of liver-invasive parasitic diseases has been investigated in murine Mesocestoides corti infection. Invasion of liver tissue by tetrathyridia resulted in extensive parenchymal destruction with fibrosis. In association with this, undetoxified endotoxin, in potentially biologically active concentration, was found on peritoneal macrophage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Mice which had received either J558-MCSF or J558L cells the day before were injected once a day for 20 days with IFN-y (between 100 and SO00 unitdinjection) and/or LPS (100 ng or 1 pg). Both reagents have been shown to be systemically effective when applied at these concentrations [18] and we could confirm the systemic effect of IFN-y in our experimental setting. In accordance with reports by others [19], daily i.p.…”
Section: Resultssupporting
confidence: 68%
“…Mice which had received either J558-MCSF or J558L cells the day before were injected once a day for 20 days with IFN-y (between 100 and SO00 unitdinjection) and/or LPS (100 ng or 1 pg). Both reagents have been shown to be systemically effective when applied at these concentrations [18] and we could confirm the systemic effect of IFN-y in our experimental setting. In accordance with reports by others [19], daily i.p.…”
Section: Resultssupporting
confidence: 68%
“…Th1-immune responses have been reported as larvicidal for tissue-dwelling helminths, therefore to overcome the type-1 immune response is necessary for establishment of the long-term infection (2,12,14,30). However, dysregulated inflammatory responses might be analogically detrimental to the host (31).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that IFN‐γ injections have larvicidal potential in mice. From this, a critical role for a Th1‐immune response in limiting parasite burden had been suggested although host IFN‐γ production has not been convincingly analyzed . In contrary, a persistently high pro‐inflammatory immune response was found to be associated with increased host lethality during M. vogae infection .…”
Section: Introductionmentioning
confidence: 99%
“…, highlighting the relevance of our observation in the general understanding of the host immunosuppression by metacestodes. Given the host protective role of IFN‐γ during experimental infection with M. corti tetrathyridia and considering the control of IFN‐γ production by dendritic cell‐derived IL‐12 , the limitation of BMDC production of IL‐12 by M. corti tetrathyridia should be beneficial to the parasite as it should consequently limit the host IFN‐gamma mediated‐inflammatory and larvicidal response .…”
Section: Discussionmentioning
confidence: 99%